Relaxation behavior of biaxially stretched PLA film during the heat setting stage - Xie, Zhenyan; Liao, Guangkai; Liu, Jiaxin; Li, Bowen; Cui, Lingna; Liu, Yuejun (Frontiers in Materials, 2023)
In this paper, the relaxation behavior of polylactic acid (PLA) film in heat setting stage of biaxial stretching was studied. Firstly, the PLA casting films were stretched synchronously in different ratios. It was found that the Machine direction (MD) and Transverse direction (TD) stress relaxation curves exhibited a separation trend with the increase of stretching ratio, and the relaxation amplitude increased gradually. Then, the stress relaxation curves were fitted by the expansion exponential equation (KWW equation). The results showed that the coefficient which used to characterize the homogeneity of stress relaxation increased with the increase of stretching ratio, and the homogeneity in MD was better than that in TD. Finally, we analyzed the evolution of rheological units and the activation energy spectrum during the stress relaxation. It was found that the volume of rheological units gradually decreased with the increase of stretching ratio. The activation energy spectrum exhibited a Gaussian distribution, and the symmetry axis of distribution curves shifted to the high energy. The above results would be of great significance for further understanding the deformation mechanism of PLA film during biaxial stretching, and providing theoretical guidance for the preparation of high-performance BOPLA films.